Lithium treatment in bipolar adolescents: a follow-up naturalistic study - Masi G (Dove Medical Press, 2018)
Gabriele Masi,1 Annarita Milone,1 Giulia Scrinzi,2 Maria Mucci,1 Valentina Viglione,1 Gabriella Bruni,1 Stefano Berloffa,1 Simone Pisano3 1IRCCS Stella Maris Foundation, Developmental Psychiatry and Psychopharmacology Unit, Pisa, Italy; 2Child Neuropsychiatry Unit, Department of Surgical Sciences, Dentistry, Gynecology and Pediatrics, University of Verona, Verona, Italy; 3Clinic of Child and Adolescent Neuropsychiatry, Department of Medicine and Surgery, University of Salerno, Salerno, Italy Background: Although lithium is currently approved for the treatment of bipolar disorders in youth, long term data, are still scant. The aim of this study was to describe the safety and efficacy of lithium in referred bipolar adolescents, who were followed up at the 4th (T1) and 8th (T2) month of treatment.Methods: The design was naturalistic and retrospective, based on a clinical database, including 30 patients (18 males, mean age 14.2±2.1 years).Results: Mean blood level of lithium was 0.69±0.20 mEq/L at T1 and 0.70±0.18 mEq/L at T2. Both Clinical Global Impression-Severity (CGI-S) and Children Global Assessment Scale (C-GAS) scores improved from baseline (CGI-S 5.7±0.5, C-GAS 35.1±3.7) to T1 (CGI-S 4.2±0.70, C-GAS 46.4±6.5; P<0.001), without significant differences from T1 to T2. Thyroid-stimulating hormone significantly increased from 2.16±1.8 mU/mL at baseline to 3.9±2.7 mU/mL at T2, remaining within the normal range, without changes in T3/T4 levels; two patients needed a thyroid hormone supplementation. Creatinine blood level did not change. No cardiac symptoms and electrocardiogram QTc changes occurred. White blood cell count significantly increased from 6.93±1.68 103/mmc at baseline to 7.94±1.94 103/mmc at T2, and serum calcium significantly increased from 9.68±0.3 mg/dL at baseline to 9.97±0.29 mg/dL at T2, both remaining within the normal range; all the other electrolyte levels were stable and normal during the follow-up. The treatment with lithium was well tolerated, probably due to the relatively low lithium blood levels. Gastrointestinal symptoms (16.7%), sedation (9.7%) and tremor (6.4%) were the most frequently reported side effects.Conclusion: Lithium was effective and safe in adolescent bipolar patients followed-up for eight months. Keywords: bipolar disorder, adolescents, lithium, safety